Factors of vascular calcification in patients with type 2 diabetes mellitus on long-term dialysis - Tatyana V. Archakova (Endocrinology Research Centre, 2020)
PURPOSE: Defining vascular calcification markers in patients on long-term hemodialysis (LTH) with type 2 diabetes mellitus (type 2 diabetes) and without type 2 diabetes. MATERIALS AND METHODS: The study was conducted in 82 patients with chronic kidney disease (CKD) (51 men, 31 women) on LTH, of which 25 patients (10 men, 15 women) had type 2 diabetes and 57 people (33 men, 24 women) had no diabetes. All patients underwent evaluation of calcium-phosphate metabolism, control of intact PTH (iPTH), inorganic phosphorus, and total calcium. All patients were tested for the level of fibroblast growth factor-23 (FGF23) in blood serum using a multi-enzyme immunoassay kit, and the correlation between these parameters and the presence of vascular calcification was evaluated. RESULTS: A correlation was found between the severity of vascular calcification and the calcium-phosphate metabolism. In the group with type 2 diabetes, there is a correlation between the level of FGF23, iPTH, inorganic phosphorus and vascular calcification. There is also a correlation between the time on LTH and the increase in the level of FGF23 in patients with type 2 diabetes. CONCLUSION: We obtained data that can indicate a more pronounced change in the vascular wall in patients with type 2 diabetes on LTH in comparison with patients without diabetes mellitus on LTH, which allows to associate high cardiovascular mortality in patients with type 2 diabetes on LTH with accelerated development of vascular calcification.